2020
DOI: 10.1093/brain/awaa188
|View full text |Cite
|
Sign up to set email alerts
|

Structural connectivity predicts clinical outcomes of deep brain stimulation for Tourette syndrome

Abstract: Deep brain stimulation may be an effective therapy for select cases of severe, treatment-refractory Tourette syndrome; however, patient responses are variable, and there are no reliable methods to predict clinical outcomes. The objectives of this retrospective study were to identify the stimulation-dependent structural networks associated with improvements in tics and comorbid obsessive-compulsive behaviour, compare the networks across surgical targets, and determine if connectivity could be used to predict cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
59
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 75 publications
2
59
0
Order By: Relevance
“…Similarly, some DBS cohorts are rare to unique world-wide and individualized connectivity data was not acquired for them. Examples include patients suffering from Alzheimer’s Disease stimulated with fornical DBS within the ADvance trials (Laxton et al, 2010), DBS cohorts suffering from rare diseases such as Tourette’s Syndrome (Johnson et al, 2019) or STN-DBS datasets for treatment of cervical dystonia (Ostrem et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, some DBS cohorts are rare to unique world-wide and individualized connectivity data was not acquired for them. Examples include patients suffering from Alzheimer’s Disease stimulated with fornical DBS within the ADvance trials (Laxton et al, 2010), DBS cohorts suffering from rare diseases such as Tourette’s Syndrome (Johnson et al, 2019) or STN-DBS datasets for treatment of cervical dystonia (Ostrem et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…This concept has since then been applied to explore connectivity associated with clinical or behavioral changes in multiple diseases (Al-Fatly et al, 2019; J. C. Baldermann et al, 2019; Johnson et al, 2019; J. Baldermann et al, 2019; de Almeida Marcelino et al, 2019; Irmen et al, 2019; Li et al, 2019; Neumann et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In OCD, connectivity with the DBS site was able to explain about 30% of variance in clinical improvement in a split-half design ( Baldermann et al, 2019b ). A similar connectome-based approachhas been used to study clinical response to DBS in chronic pain ( Fernandes et al, 2015 ), dystonia ( Corp et al, 2019 ), depression ( Choi et al, 2015 ; Riva-Posse et al,2014 ), treatment-refractory epilepsy ( Middlebrooks et al, 2018a ) and Tourette’s Syndrome ( Johnson et al, 2020 ). These studies established a direct–if correlational – link between clinical improvements and brain connectivity with the DBS site.…”
Section: Eight Opportunities Of Connectomic Neuromodulationmentioning
confidence: 99%
“…Our analysis showed significant differences within the pallidal and also within the thalamic targets ( Figure 5 ). In previous tractography studies, the CM-Pf and the CM/Voi were merged into one target, and in some cases the two pallidal targets were also regarded as one [ 19 , 22 ]. Based on our findings, all targets must be analyzed separately to provide a recommendation for lead placement or targeted stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have reported a correlation between the connectivity patterns of different DBS targets and a reduction in the symptoms of GTS patients [ 20 , 21 , 22 ]. However, most studies have focused on a single DBS target, with only one study comparing pallidal and thalamic stimulation [ 22 ]. The analyses were based either on normative structural connectome atlases or on patient-specific diffusion-weighted MRI, which complicates the comparison of the findings.…”
Section: Introductionmentioning
confidence: 99%